Lordship and faith: the English gentry and the parish church in the Middle Ages - Saul, Nigel (Oxford University Press, 2017)
"Lordship and Faith takes as its subject the many hundreds of parish churches built in England in the Middle Ages by the gentry, the knights and esquires, and the lords of country manors. Nigel Saul uses lordly engagement with the parish church as a way of opening up the piety and sociability of the gentry, focusing on the gentry as founders and builders of churches, worshippers in them, holders of church advowsons, and patrons and sponsors of parish communities. Saul also looks at how the gentry's interest in the parish church sat alongside their patronage of the monks and friars, and their use of private chapels in their manor houses. Lordship and Faith seeks to weave together themes in social, religious, and architectural history, examining in all its richness a subject that has hitherto been considered only in journal articles. Written in an accessible way, this volume makes a significant contribution not only to the history of the English gentry but also to the history of the rural parish church, an institution now in the forefront of medieval historical studies" --